2012
DOI: 10.1099/vir.0.041228-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Itk signalling in the interaction between influenza A virus and T-cells

Abstract: Although the T-cell-mediated immune response to influenza virus has been studied extensively, little information is available on the direct interaction between influenza virus and T-cells that pertains to severe diseases in humans and animals. To address these issues, we utilized the BALB/c mouse model combined with primary T-cells infected with A/WSN/33 influenza virus to investigate whether influenza virus has an affinity for T-cells in vivo. We observed that small proportions of CD4+ T-cells and CD8+ T-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…1 to 2). A recent report shows that PLC-␥1 activation is important for WSN infection in T cells, although it did not characterize the mechanism of action (30). Therefore, PLC-␥1 seems to be important for H1N1 infection in various cell types.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1 to 2). A recent report shows that PLC-␥1 activation is important for WSN infection in T cells, although it did not characterize the mechanism of action (30). Therefore, PLC-␥1 seems to be important for H1N1 infection in various cell types.…”
Section: Discussionmentioning
confidence: 95%
“…5). In the study by Fan et al, the authors have shown that WSN infection of T cells induces the PLC-␥1 activation through interleukin-2-inducible T-cell kinase (Itk), a T-cell-specific nonreceptor tyrosine kinase, to the plasma membrane (30). Taking these findings together, the mechanism by which influenza virus induces PLC-␥1 activation (and possibly other signaling molecules) may vary by viral subtypes and host cell types but is likely mediated via an upstream receptor or nonreceptor tyrosine kinase that is triggered by virus binding to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that ibrutinib may provide benefit in other inflammatory disorders, ranging from allergic asthma and atopic dermatitis to inflammatory bowel disease. 11 Moreover, it was recently demonstrated that ITK activation plays a vital role in the replication of influenza A virus in T cells 46 and is critical for HIV replication and infection cycles, making ITK a valuable target in the development of antiviral therapeutics. 10 Given the global threat of HIV and pandemic influenza, ibrutinib's potential utility as an irreversible ITK inhibitor should be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the underlying immune mechanisms that protect against various strains of influenza virus, only limited information is available on the direct interaction between influenza virus strains and host T cells [12,13]. Studies with highly virulent influenza A virus strains resulted in the destruction of lymphocytes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with highly virulent influenza A virus strains resulted in the destruction of lymphocytes (e.g. RP9 avian lymphocytes cell line) and histopathological necrosis of lymphoid tissues [12,14,15]. However, whether influenza virus is able to propagate in human lymphocytes remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%